Structural characterization, DFT-based electronic analysis, Hirshfeld surface study, molecular docking, and in silico drug-likeness evaluation of N-(4-(3-methyl-3mesitylcyclobutyl)-1H-imidazol-2-yl)acetamide - Simsek, Okan; Kansiz, Sevgi; Yilmaz, Ibrahim; Cukurovali, Alaaddin; Dincer, Muharrem (Elsevier, 2026)
N-(4-(3-methyl-3mesitylcyclobutyl)-1H-imidazol-2-yl)acetamide (MMCIA), a cyclobutane-imidazole derivative, was synthesized and investigated through an integrated experimental and theoretical approach to elucidate its structural, electronic, and pharmacological features. Single-crystal X-ray diffraction analysis revealed that MMCIA crystallizes in the triclinic P1 space group, with the crystal packing stabilized by a cooperative network of N-H center dot center dot center dot O and N-H center dot center dot center dot N hydrogen bonds, supported by C-H center dot center dot center dot pi interactions. Hirshfeld surface analysis quantified the dominant intermolecular contacts, indicating that H center dot center dot center dot H (69.1%) and C center dot center dot center dot H/H center dot center dot center dot C (11.9%) interactions play a major role in lattice stabilization. Density Functional Theory (DFT) calculations at the B3LYP/6-311G(d,p) level further supported the molecular stability, revealing a HOMO-LUMO energy gap of 3.72 eV, a chemical hardness of 1.86 eV, and a relatively high electrophilicity index of 12.2 eV, indicating moderate kinetic stability together with a pronounced electrophilic character. Molecular electrostatic potential mapping and reduced density gradient analysis provided complementary insight into the distribution of electrophilic/nucleophilic regions and the nature of weak non-covalent interactions governing molecular stability. Molecular docking studies against tubulin A predicted a favorable binding affinity of -7.87 kcal/mol, corresponding to an estimated inhibition constant (Ki) of approximately 1.7 mu M., indicating potential inhibitory activity. In silico ADME and drug-likeness evaluations, including the BOILED-Egg model, suggested high gastrointestinal absorption, blood-brain barrier permeability, and full compliance with Lipinski's rule of five.
Keywords: Cyclobutane; Imidazole; Sc-XRD; Dft; Molecular docking; Adme